Analysis of genetic factors influencing susceptibility to dental caries by using a chromosome 2 substitution mouse strain. Issue 1 (April 2016) - Hiraki, Akiko; Shimizu, Kunihiko
Abstract: Objective: Dental caries, a major public health concern worldwide, is influenced by both environmental and genetic factors. The objective of this study was to identify genetic factors influencing susceptibility to dental caries using mouse strains that show differences in caries susceptibility. Materials and methods: We investigated whether differences in phenotypic traits (salivary secretion volume, salivary buffering capacity, submandibular gland histology, and enamel hardness) are associated with different susceptibility to dental caries in the three mouse strains C3H/HeSlc, C57BL/6Slc, and B6-Chr.2 C3H . C3H/HeSlc is resistant to dental caries. Conversely, C57BL/6Slc is highly susceptible to dental caries. B6-Chr.2 C3H was constructed by substituting chromosome 2 of C3H/HeSlc into C57BL/6Slc. We also examined the expression level of two candidate genes, Slc24a3 and Slc9a8, on chromosome 2, which are considered as regulatory factors of salivary secretion volume. Results: The salivary secretion volume of B6-Chr.2 C3H was higher than that of C57BL/6Slc, while no clear differences were observed in any other traits. Further, we found that the expression levels of Slc9a8 and Slc24a3 in the submandibular gland were significantly different between C57BL/6Slc and C3H/HeSlc or B6-Chr.2 C3H . Conclusion: We concluded that salivary secretion is one of the main factors affecting susceptibility to dental caries, and that the genes influencing salivary secretion volume are located on chromosome 2 in mice and play an important role in susceptibility to dental caries.